Challenging dogmas: How transgenerational epigenetics reshapes our views on life. Issue 1 (26th April 2021) - Wang, Harrison D.; Allard, Patrick
Abstract: The emergence of the field of transgenerational epigenetics inheritance (TEI) has profoundly reshaped our understanding of the relationships between environment, soma, and germ cells as well as of heredity. TEI refers to the changes in chromatin state, gene expression, and/or phenotypes that are transmitted across several generations without involving changes to the DNA sequences. TEI has direct connections with, and feeds from, the fields of molecular biology, genetics, developmental biology, and reproductive biology, among others. However, the expansion of TEI‐related research, has profoundly reshaped boundaries within each field and often led to the erosion of theories and concepts considered as tenets of biology. We first explore how the molecularization of biology has shifted the definition of epigenetics to include the notion of heredity and how epigenetics has refined our understanding of the central dogma of biology. The demonstrated transfer of environmental information from soma to germ cell through extracellular vesicles and subsequent alteration of health outcomes in offspring has put a definite end to the long‐held principle of the Weismann barrier. TEI has also simultaneously led to the revival of the inheritance of acquired characteristics while further eroding the concept of an epigenetic "blank slate" in mammals. Using an historical framework, and via the exploration of central studies in the field, in this perspective article, we will draw a compelling argument for the revolutionary aspect of TEI in biology. Abstract : Research Highlights: TEI has benefited from and hastened the erosion of several tenets of biology including the central dogma of molecular biology and the Weismann barrier. Conversely, TEI has lent credence to Lamarckian views and soft inheritance